Reassessing the polyphase Neoproterozoic evolution of the Punta del Este Terrane, Dom Feliciano Belt, Uruguay - Silva Lara, Hernan (2022)
Some recent models challenge the position and extension of the assumed oceanic basins formed through the break-up of Rodinia, and the tectonic processes involved in the Gondwana assembly, making the investigation of the Early Neoproterozoic record of great relevance. Within the South-American Atlantic margin, the Punta del Este Terrane (PET) of the Dom Feliciano Belt (DFB) comprises a unique Tonian to Ediacaran record, and has a strategic position to reconstruct spatio-temporal relationships with the southern African orogenic belts. Novel zircon U–Pb and Lu–Hf data from the PET basement orthogneisses display Tonian magmatic ages (805–760 Ma) and Hf isotopic signatures indicative of mainly crustal/metasedimentary sources, (Nd TDM ages: 2.2–1.9 Ga, and εHf(t): − 12 to − 4). The basement paragneisses yielded late Paleoproterozoic to Neoproterozoic U–Pb ages, but dominantly positive εHf(t) values. The presented results confirm the correlation of the PET with the Coastal Terrane of the Kaoko Belt, and discard the idea of the Nico Pérez Terrane as a source. Detrital zircon U–Pb and Lu–Hf data from the Rocha Formation yielded a main peak at ca. 660 Ma, with the Neoproterozoic grains showing a εHf(t) between + 1 and + 14. The deposition age of the Rocha Formation is constrained by the youngest detrital zircon age peak (660 Ma), and the beginning of the deposition of the Sierra de Aguirre Formation (580 Ma). The data indicate common sources with the Marmora Terrane, and it is thus proposed that the Rocha Formation belongs to the Gariep Belt, and it was juxtaposed during the Ediacaran to the DFB.